A RARE CASE OF SHPRINTZEN-GOLDBERG SYNDROME - Chitran, Parvathy; L.S, Sreela; Mathew, Philips; Prasad, Twinkle S (Journal of Ayub Medical College Abbottabad, 2021)
Shprintzen-Goldberg syndrome is a relatively rare congenital connective tissue type of disorder with a constellation of dysmorphic features including craniosynostosis, craniofacial, skeletal, cardiovascular and neurological abnormalities. We present the case-report of a 5-year-old boy with Shprintzen-Goldberg syndrome and a brief review of literature pertaining to this condition. The patients with Shprintzen-Goldberg syndrome show a considerable phenotypic overlap with other craniosynostosis syndromes. So, a meticulous evaluation of these patients should be performed for a prudent diagnosis. Since these patients present with multiple systemic conditions,a multidisciplinary approach should be planned for their management. Keywords: Brachycephaly; Cleftpalate; Craniosynostosis; Cryptorchidism; Hypertelorism; Uvula